Molecular detection of hemoplasmas and genetic diversity of Anaplasma marginale in a dairy water buffalo (Bubalus bubalis) farm from southeastern Brazil - Secato, Caroline Tostes [UNESP]; Gonçalves, Luiz Ricardo; de Souza Ramos, Inalda Angélica [UNESP]; do Amaral, Renan Bressianini [UNESP]; Mongruel, Anna Claudia Baumel [UNESP]; da Silva, Thiago Merighi Vieira [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2025)
Brazil has the largest water buffalo (Bubalus bubalis) herd outside the Asian continent. As buffalo farming has become an economically important activity and has grown in recent years, studies are needed on the occurrence of pathogens shared between cattle and water buffaloes, since, in most locations, these animals graze together. The aim of this study was to investigate the molecular occurrence of hemoplasmas and genetic diversity of Anaplasma marginale in water buffaloes and associated ectoparasites in southeastern Brazil. DNA was extracted from 81 blood samples, 165 Rhipicephalus microplus ticks, and 92 Haematopinus tuberculatus lice from water buffaloes. In 16S rRNA gene-based PCR assays, 25.9 % (21/81) of buffalo blood samples were positive for 'Ca. M. haemobos', 50.6 % (41/81) for M. wenyonii, and 23 (28.4 %) for both hemoplasma species. In the A. marginale qPCR targeting the msp1β gene, 46.9 % of buffalo blood samples, 1.08 % of louse samples, and 49.1 % of tick samples were positive. High genetic diversity of A. marginale, including 10 new strains and three previously reported strains, was found in water buffaloes and associated ticks in the studied region. Anaplasma marginale genotype E was the most prevalent. Genetic diversity indices indicated that the short sequence repeats (SSRs) of A. marginale msp1α were highly diverse within the studied region, but showed low dispersion to other regions of the country. The absence of anemia in water buffaloes co-infected with M. wenyonii, 'Ca. M. haemobos', and A. marginale suggests a possible resistance of these animals to infection by these agents.